2023
DOI: 10.1007/s00167-023-07324-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mediolateral gap difference on postoperative outcomes in navigation-assisted total knee arthroplasty using an ultracongruent insert and the medial stabilising technique

Abstract: PurposeThis study was aimed to compare the clinical, functional, and radiographic outcomes between symmetric and asymmetric extension and mediolateral gap balance after navigation‐assisted (NA) total knee arthroplasty (TKA) using ultracongruent (UC) insets and the medial stabilising technique (MST). MethodsIn all, 363 knees of 275 patients who underwent mechanical alignment‐target NA TKA with MST between January 2015 and December 2017 were analysed. Patients were divided into balanced (extension mediolateral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The average follow-up in group CP was 44 ± 9.9 months (range 37-61) and in group PS was 42.7 ± 5.5 months (range 36-43) ( P = .06). The average insert thickness in the CP group was 10.7 ± 2.1 mm [ 3 , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ], while in PS group it was 10.4 ± 1.6 mm [ 3 , [8] , [9] , [10] , [11] , [12] , [13] , [14] ] (range 9-15) ( P = .36) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average follow-up in group CP was 44 ± 9.9 months (range 37-61) and in group PS was 42.7 ± 5.5 months (range 36-43) ( P = .06). The average insert thickness in the CP group was 10.7 ± 2.1 mm [ 3 , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ], while in PS group it was 10.4 ± 1.6 mm [ 3 , [8] , [9] , [10] , [11] , [12] , [13] , [14] ] (range 9-15) ( P = .36) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A CP insert with primary femoral component is also effectively used in valgus knees where medial laxity persists in extension and flexion after valgus deformity is corrected to ±2 degree with the help of computer assisted surgery (CAS) [ 15 ]. Similar to varus knees, CP insert is not a substitute for inadequate soft tissue balancing in a valgus knee but only an adjunct to achieve more stability and maintain M-L gap difference between ≤2 mm throughout the arc of motion ( Figure 6 , Figure 7 , Figure 8 ) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the severity of the preoperative varus alignment was closely related to the mediolateral gap difference [ 11 ]. One major concern in allowing for lateral laxity is the possibility of hyperextension after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The deep MCL was released to create a space for implantation. Other medial soft tissue releases were not performed and lateral physiological laxity was allowed to avoid excessive medial release, as in previous studies [ 5 , 11 ]. Distal femoral and proximal tibial cuttings were performed in a plane perpendicular to the mechanical axes of the femur and tibia, respectively.…”
Section: Methodsmentioning
confidence: 99%